Assembly of highly-sensitive capacitive flexible pressure sensor based on BTO NWs -TPU porous composites film. (November 2022) - Nie, Lifan; Zhang, Long; Di, Xinpeng; Liu, Qingyi; Zhang, Zi'ang; Zhou, Quan; Dong, Zhaobo; Song, Zhidan; Zhang, Shaohui; Pan, Gebo
Abstract: In this paper, an effective strategy for fabricating high-sensitive flexible capacitive pressure sensors is proposed. By combining the BaTiO3 nanowires (BTO NWs), which have an ultra-high aspect ratio, with thermoplastic polyurethane (TPU), a flexible porous dielectric layer is constructed for the construction of a high-sensitive capacitive pressure sensor, and the sensor's sensing performance was also explored deeply. Results show that the functionalized BTO NWs uniformly disperse in the polymer matrix, which can be beneficial to increasing the permittivity of the composites, thus enhancing the performance of the capacitive pressure sensor. The fabricated porous BTO-TPU capacitive pressure sensor exhibits a high sensitivity (∼1.47 kPa −1 ) at the pressure range of 0–10 kPa, fast response (∼86 ms), and excellent durability under 10, 000 cycles, suggesting that the porous dielectric helps to improve the capacitance variation of the device. Furthermore, the sensing behavior of the sensor is verified for human activities monitoring by attaching the sensor to the joints of the human. In addition, this work also reveals the expansive application prospect of BTO NWs in flexible wearable electronics. Highlights: BTO NWs-TPU porous composite dielectric is used to assemble the flexible capacitive pressure sensors. Porous BTO-TPU capacitive pressure sensor exhibits a high sensitivity, fast response, and excellent stability. The BTO-TPU porous structure helps to enhance the capacitance variation of the device.